Preparing Gifted Students for College Success within the High School Science Classroom - Boehler, Julia Thomas (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
College is a crucial step for many students in order to obtain their desired career. Research has shown that often gifted students have poorer college adjustment than their non-gifted peers. Gifted students have unique needs in high school classrooms, and when these needs are not met, they will not develop important skills they need for college success. It is the role of all high school teachers, including science teachers, to not only help their students achieve in high school, but also to prepare them for success following graduation. This article discusses the areas gifted students often lack skills in as well as instructional strategies that high school science teachers can use to help their gifted students develop these skills. By using a combination of strategies like homogenous grouping, higher-order cognitive tasks, differentiation and Project Based Learning, high school science teachers will better prepare their gifted students for success in college.